Designed or made? Questioning public space as conflicting in South Africa's townships' top-down development : the case of Kliptown, Soweto - Gatome, Mary Clare (My University, 2016)
The broader aim of this study is to see how these challenges can be dealt with the objective of making public spaces that is meaningful to residents in socially complex and economically challenged areas. The study illuminates the challenges in designing a typology that is as open and volatile as public open space, and in particular the square, that is, conceived space. It also seeks to understand what form public open space and social spaces take on, and how they are used in ways that are peculiar to the township context. the research seeks to establish design concepts to develop WSSD through involvement of the community and being more responsive to its context, can become a meaningful space. [Abbreviated Abstract. Open document to view full version]
Keywords: Public spaces--South Africa--Soweto; City planning--South Africa--Johannesburg--Soweto; Community development--South Africa--Johannesburg--Soweto